If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
y = (2*(6*y-9))/18 // - (2*(6*y-9))/18
y-((2*(6*y-9))/18) = 0
(-1/9)*(6*y-9)+y = 0
y-1/9*(6*y-9) = 0
y-1/9*(6*y-9) = 0
1/3*y+1 = 0
1/3*y+1 = 0
1/3*y+1 = 0 // - 1
1/3*y = -1 // : 1/3
y = -1/1/3
y = -3
y = -3
| 37x-1+40=49x+3 | | x+3.75=0.25x | | (-2/2)^2 | | 3+3n=9+2n+4n | | 2y-5=3x | | 6.3x-1=5.3x | | y/7=91 | | 10x-2+12x=64 | | 56x+63=7(7x+8)+7x+7 | | -(x-9)=3x | | 3x-5+2x-3+15-x=35 | | 5P+7=15+4P | | 0.5x-2.3=0.2 | | 5(2x+3)=21 | | 0.03(x+2)-0.5(X+2)=0.2x-0.4 | | x+5/x-7=x-2/x+2 | | 11x+11+6x+6=136 | | x+5/x-7=x-2/x | | x+5+22=4x-9 | | 3a+4ab=9a | | p=v2/r | | 3k^2-5k+1=0 | | 4+7(7p+5)=39 | | 3a+4ab= | | 68x+2+28=82x+1 | | -4(5t-3)+5t=4t-9 | | [40+10r]=27-3r | | 32-x/5=x/3 | | 3/8x+7/8=-1 | | 2x-8+5=0 | | z/3=21 | | 2s+7=3-s |